Complex Perioperative Decision-Making: Liver Resection in a Patient with Extensive Superior Vena Cava/Right Atrial Thrombus and Superior Vena Cava Syndrome - Benjamin Kloesel; Robert W. Lekowski (Case Reports in Anesthesiology)
The perioperative management of patients suffering from extensive superior vena cava (SVC) thrombus complicated by SVC syndrome presents unique challenges. The anesthesiologist needs to be prepared for possible thrombus dislodgement resulting in pulmonary embolism and also has to assess the need for fluid resuscitation given the dangers of massive intravenous fluid application via the upper extremities. We present our perioperative approach in management of a patient scheduled for right hepatectomy who was previously diagnosed with extensive SVC and right atrial (RA) thrombus complicated by SVC syndrome.